SUMBER INFORMASI, PENGETAHUAN DAN SIKAP PENCEGAHAN REMAJA TERHADAP PENCEGAHAN KEHAMILAN BAGI REMAJA DI KOTA JAMBI TAHUN 2021 - Novi Berliana; T Samsul Hilal; Rosa Minuria (Sekolah Tinggi Pariwisata Mataram, 2021)
Adolescence is a period of rapid growth and development both physically, psychologically, and intellectually. The characteristics of adolescents who have a great curiosity, like adventure and challenges and tend to dare to take risks without careful consideration, one of the problems that occur during adolescence such as sexuality problems, unwanted pregnancy (KTD) and abortion, infection with sexually transmitted diseases (STDs). ), and drug abuse. The design of this study used descriptive analytic. With a Cross Sectional approach where the research will be conducted aims to determine the relationship between knowledge of reproductive health and attitudes towards prevention of teenage pregnancy in Jambi City. Respondents were teenagers aged 13 to 17 years as many as 76 people